Internet of Robotics Things (IoRT) Based Integration of Robotic Applications for Advanced Research - HM Verma (Wasit Journal of Computer and Mathematics Science, 2021)
IoT and robotics industries are united to create the Internet of Robotics Things (IoRT). IoRT is the idea of intelligent machines monitoring the environment around them and using local and distributed intelligence to decide on courses of action and making decisions accordingly. IOT is a network of devices that are connected to the internet, including devices and equipment connected by sensors. These elements are essential for businesses trying to drive customer facing innovation, data-driven decisions, new applications, digital transformation, business models and revenue streams. Robots need to maintain great flexibility to react to unexpected conditions. AI helps these robots to deal with any unforeseen circumstances. Robotics and Simulation are key elements in the solutions of advancing manufacturing and production. Many people often think of IoT and robotics technologies in separate fields but they have been getting increasingly close in recent years. The In this way, such processes are used to avoid the loss of human life and the automation of processes which need high performances. Robotic and simulated application have been successfully deployed to functions in real world scenarios that man will not be able to accomplish such as study of volcanoes, and space center on its own. Furthermore, the robotic implementations give robots the opportunity to efficiently and safely function in the adverse conditions without being injured physically.